Assembly of Ordered Polystyrene Nanoparticles on Self-Assembled Monolayers - Shalev, Ortal Lidor; Hagit, Hagit; Mastai, Yitzhak (Journal of Research Updates in Polymer Science, 2016)
Spontaneous assembly of nanoparticles onto a surface is a promising bottom-up concept for the fabrication of new functional materials that can be used for various applications in the nanotechnology. In this paper, we describe a system based on gold/polystyrene (Au/PS) Janus particles arranged onto Au self-assembled monolayer (SAM) of 1-dodecanthiol (NDA). The micro-size Au/PS Janus particles are self-assembled onto Au surface and are dissolved into polystyrene (PS) nanoparticles. The SAM of NDA plays two different roles; it dissolves the original Au/PS Janus particles and organizes the PS nanoparticles onto the Au surface. Overall, our proposed method for the assembly of large-scale area nanoparticles can be extended for further uses in the surface science.